Frequency, severity and risk factors for urinary and faecal incontinence at 4 years postpartum: a prospective cohort. (14th July 2015) - Gartland, D; MacArthur, C; Woolhouse, H; McDonald, E; Brown, SJ
Abstract : Objectives: To investigate frequency, severity and risk factors for urinary incontinence and faecal incontinence 4 years after a first birth. Design: Prospective pregnancy cohort study. Setting: Melbourne, Australia. Sample: A total of 1011 nulliparous women recruited in early pregnancy. Methods: Participants were followed up at 32 weeks of gestation; then at 3, 6, 9 and 12 months and 4 years postpartum. Main outcome measures: Frequency and severity of urinary and faecal incontinence. Results: At 4 years, 29.6% of women reported urinary incontinence and 7.1% reported faecal incontinence. Compared with women having only spontaneous vaginal births, women who delivered exclusively by caesarean section were less likely to have urinary incontinence at 4 years postpartum (adjusted odds ratio 0.4, 95% confidence interval 0.3–0.6). Women who reported urinary incontinence before or during the index pregnancy, and those experiencing symptoms in the first year postpartum had increased odds of incontinence at 4 years, with the highest odds (6–12 times higher) among women who had previously reported moderate or severe symptoms. The odds of reporting faecal incontinence at 4 years were two to six times higher for women experiencing symptoms in pregnancy, and around four to eight times higher for those with symptoms in the first year postpartum. Conclusion: Urinary and faecal incontinence are prevalent conditions 4 years after a first birth. Women reporting urinary or faecal incontinence during pregnancy had markedly higher odds of reporting symptoms at 4 years postpartum, suggesting a need for further investigation and elucidation of aetiological pathways involving nonbirth‐related risk factors. Tweetable abstract: Moderate/severe incontinence prevalent 4 years after first birth in population cohort. Prior symptoms are biggest predictor. Tweetable abstract: Moderate/severe incontinence prevalent 4 years after first birth in population cohort. Prior symptoms are biggest predictor.